A High Secured Ecc Based Iot Audiometric System For Cloud Based Dynamic Sensor Domain Environment - et. al., N.Bhaskar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper is made based on the requirement of different domain users for effective hearing system. The system uses different devices to enhance the audio capability of different users at different application environment. The system uses IoT devices, sensors and different gateways for effective use of IoT based systems. The system will enhance the hearing capability of all users at different conference or personal or professional environments for the effective hearing capability among different hearing capabilities. It provides the environment to increase or decrease the volume of the source system based on the hearing capability of participants in the hearing environment. It can be used in any domain like conferences, home environment, education institutions and at public locations. It also adopts a security algorithm to protect the customer’s data in encrypted format at cloud system. It recognizes the candidate at any time based on the ID assigned to an individual.